(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
In this research, numerical modeling is conducted on free convective flow inside a trapezoidal domain with sinusoidal material and temperature allocations at both inclined boundaries using Buongiorno’s nanofluid. The model considers thermophoresis with Brownian activity effects taking place in the flow, temperature as well as concentration contours. Non-uniform nanoparticle solid concentration and temperature allocations have been imposed at both inclined surfaces. Top and bottom parallel surfaces have been kept as adiabatic. All the walls have been considered as no-slip and impermeable. The leading equations in addition border conditions are initially converted into a dimensionless pattern by a suitable similarity transformation and then resolved arithmetically employing the finite element technique with Galerkin’s residual. Buongiorno’s model of nanofluid on thermal and material transports, and flow structure has been investigated in detail. Outcomes have been displayed in the form of velocity, temperature, and concentration contours with various governing factors like Brownian action, Lewis number, Buoyancy relation, thermophoresis, Rayleigh number, Prandtl number, etc. Also, the rate of thermal transport has been calculated. The thermophoresis and Brownian effects on velocity, heat, and material fields are identified and finally, the flow, heat, and concentration controlling parameters for a specific material and thermal transport applications inside a trapezium-shaped cavity are obtained. Result demonstrates that the increase of Brownian action guides to enhance thermal transport by 34.75 and 34.27% for the right and left walls, respectively.